Light-Driven CO2 Reduction by Co-Cytochrome b562 - Alcala-Torano, Rafael; Halloran, Nicholas; Gwerder, Noah; Sommer, Dayn J.; Ghirlanda, Giovanna (Frontiers in Molecular Biosciences, 2021)
The current trend in atmospheric carbon dioxide concentrations is causing increasing concerns for its environmental impacts, and spurring the developments of sustainable methods to reduce CO2 to usable molecules. We report the light-driven CO2 reduction in water in mild conditions by artificial protein catalysts based on cytochrome b562 and incorporating cobalt protoporphyrin IX as active site. Incorporation into the protein scaffolds enhances the intrinsic reactivity of the cobalt porphyrin towards proton reduction and CO generation. Mutations around the active site modulate the activity of the enzyme, pointing to the possibility of further improving catalytic activity through rational design or directed evolution